Data mining techniques : for marketing, sales, and customer relationship management - Berry, Michael J. A. (Wiley, 2004)
* Packed with more than forty percent new and updated material, this edition shows business managers, marketing analysts, and data mining specialists how to harness fundamental data mining methods and techniques to solve common types of business problems* Each chapter covers a new data mining technique, and then shows readers how to apply the technique for improved marketing, sales, and customer support* The authors build on their reputation for concise, clear, and practical explanations of complex concepts, making this book the perfect introduction to data mining.